Microwave hybrid sintering of Al2O3 and Al2O3–ZrO2 composites, and effects of ZrO2 crystal structure on mechanical properties, thermal properties, and sintering kinetics. Issue 7 (May 2020) - Khalid, Muhammad Waqas; Kim, Young Il; Haq, Muhammad Aneeq; Lee, Dongju; Kim, Bum Sung; Lee, Bin
Abstract: Structural ceramics such as Al2 O3 and Al2 O3 –ZrO2 composites are widely used in harsh environment applications. The conventional sintering process for fabrication of these ceramics is time-consuming method that requires large amount of energy. Microwave sintering is a novel way to resolve this problem. However, to date, very limited research has been carried out to study the effects of different ZrO2 crystal structures on Al2 O3 –ZrO2 composites, especially on the sintering kinetics, when fabricated by microwave sintering. The microwave hybrid sintering of Al2 O3 and Al2 O3 –ZrO2 composites was performed in this study. Tetragonal zirconia and cubic zirconia were used as two different reinforcements for an α–alumina matrix, and the mechanical and thermal properties were studied. It was found that Al2 O3 experienced a remarkable increase in fracture toughness of up to 42% when t-ZrO2 was added. Al2 O3 –c-ZrO2 also showed increased fracture toughness. The sintering kinetics were also thoroughly investigated, and the average activation energy values for the intermediate stage of sintering were estimated to be 246 ± 11 kJ/mol for pure Al2 O3, 319 ± 71 kJ/mol for Al2 O3 –c-ZrO2, and 342 ± 77 kJ/mol for Al2 O3 –t-ZrO2 . These values indicated that the activation energy was increased by the addition of either type of ZrO2, with the highest value shown by Al2 O3 –t-ZrO2 .